Enhancing performance of MAODV routing protocol for wireless mesh network using integrated multiple metrics technique (IMMT) - Anwar, Farhat; Hassan Abdalla Hashim, Aisha; Bari, S.M. Sadakatul; Akhtaruzzaman, Md.; Masud, Mosharrof Hussain; Naeem, Jannatul; Azad, Md. Saiful; Rahman, Md. Arafatu (Scientific & Academic Publishing, 2012)
Abstract Customarily, the design of an efficient routing protocol for Wireless Mesh Networks (WMNs) demands suffi-cient consideration of the pertinent features. This is due to the fact that WMNs can be permanent or semi-permanent networks. Moreover, a reliable path from the source to the destination can be maintained using an improved and better performance metrics. Currently, the most widely used performance metric is the minimum hop-count which is based on the assumption that communication links are either working well or not working at all. This assumption is true for wired networks however this is impractical for wireless networks where numerous links suffer from intermediate loss ratios, low throughput, inter-ference and other inherent limitations. Consequently, researchers have proposed a number of performance metrics for WMNs. It has also been shown that integrating multiple performance metrics into a routing protocol is effective for attaining optimal performance since it is highly probable that a single performance metric will not be able to satisfy the comprehensive re-quirements of WMNs. This paper presents a technique of integrating multiple routing metrics in order to optimize the per-formance of a routing protocol. The proposed technique is implemented on Multicast Ad-hoc On-Demand Distance Vector (MAODV) routing protocol. Simulation results show a statistically significant performance improvement over standard MAODV for WMNs. Keywords Wireless Mesh Networks, MAODV, Performance Metrics, Routing Protocol, IMMT, WMN